2022
DOI: 10.3832/ifor4033-015
|View full text |Cite
|
Sign up to set email alerts
|

Variability of tolerance of Wild cherry clones to PEG-induced osmotic stress in vitro

Abstract: The effects of drought simulated via osmotic stress induced by polyethylene glycol (PEG) in the growing medium were examined on two Wild cherry (Prunus avium L.) clones (6A and 8A) based on thirteen morphometric, physiological, and biochemical traits. The shoot tips were exposed to two PEG concentrations (20 and 50 g L -1 ) in growing medium designed for micropropagation with axillary buds. The results showed that all morphological and physiological traits were significantly reduced, indicating a strong detrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…A concentration of 200 μM caused a 47% increase in phenolic compounds in the roots of Populus deltoides and a 38–168% increase in the bark of Populus ×euramericana , Populus nigra , and Populus popularis , while in the leaves of Populus nigra, phenolic content was 67% higher compared to control plants [ 59 ]. Phenolic compounds increase plant tolerance to various abiotic stress factors, such as temperature fluctuations, the presence of heavy metals [ 68 ], and water deficit [ 69 , 70 ], in addition to their importance in allelopathic relationships and herbivore defense [ 71 ]. Furthermore, other publications revealed that the total polyphenolic content of many plants reduced during abiotic stresses [ 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…A concentration of 200 μM caused a 47% increase in phenolic compounds in the roots of Populus deltoides and a 38–168% increase in the bark of Populus ×euramericana , Populus nigra , and Populus popularis , while in the leaves of Populus nigra, phenolic content was 67% higher compared to control plants [ 59 ]. Phenolic compounds increase plant tolerance to various abiotic stress factors, such as temperature fluctuations, the presence of heavy metals [ 68 ], and water deficit [ 69 , 70 ], in addition to their importance in allelopathic relationships and herbivore defense [ 71 ]. Furthermore, other publications revealed that the total polyphenolic content of many plants reduced during abiotic stresses [ 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…By regulating the transfer between soil and roots and between roots and leaves, concentrations of these elements are kept within a normal range in their tissue ( Pandey et al., 2012 ; Mukhopadhyay et al., 2017 ; Kostić et al., 2022b ). Tolerant plant species also respond to abiotic stress by increasing their antioxidant capacity, which helps them to maintain a normal cellular balance between production and binding, degradation, and neutralisation of ROS by enzymatic or non-enzymatic antioxidants (carotenoids and anthocyanins) and secondary metabolites (phenols) ( Cervilla et al., 2012 ; Gajić et al., 2020 ; Kebert et al., 2022 ; Vuksanović et al., 2022 ). Intolerant species exibit decreased antioxidant capacity and fewer mechanisms for detoxification in relation to ROS production, resulting in chain reactions in which free radicals damage important biomolecules, such as chloroplast pigments, lipids, and nucleic acids, oxidatively.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro cultures have been used to assess drought tolerance in numerous plant species: potato (Solanum tuberosum L.) (Hanaśz et al, 2022), rice (Biswas et al, 2002), guava (Psidium guajava L.) (Youssef et al, 2016), blueberry (Vaccinium corymbosum L.) (Molnar et al, 2022), "Mexican lime" (Citrus aurantifolia (Christ.) Swingle) (Jafari and Shahsavar, 2022), Mexican marigold (Tagetes minuta L.) (Babaei et al, 2021), Stevia rebaudiana (Bertoni) (Hajihashemi and Sofo, 2018), Agave salmiana (Puente-Garza et al, 2017), Wild cherry (Prunus avium L.) (Vuksanovićet al, 2022), olives (Olea europaea L.) (Silvestri et al, 2017), kiwifruit (Actinidia chinensis Planch. ), (Wu et al, 2019), fig tree (Ficus carica L.) (Abdolinejad and Shekafandeh, 2022) and euramerican poplar (Popovićet al, 2017).…”
Section: Introductionmentioning
confidence: 99%